(3QSGdI aj eGgjI GdSbfbhR (B( (3GdTbfbhQ (B)s - (3gHI Gddg Hf RjO Hf MSf Hf GaQGFje Hf jYbhH Hf LejY GdGSQGFjdj, GdeJWHH GdeUQj,J (B594 (3g` s
(3ChdgG (B:s
(3bGd GdSbfbhR gh MjhGf TOjO GdTHg HGdhQd jhLO ai GdQeGd GdJi Jdi fjd eUQ hCcKQ Pdc ai fhGMi UYjOgG s
(3BNQgG (B:s
(3hWQjb GdJNjd dge ai Pdc hSGY ddWHjH GdMGPb hGSJjaGA Gdbhd ajg NGQL Yf ZQV gPg GdQSGdI hai GdPi ChQOfGg efg ajgG caGjI JeJ s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdChdis
(3bhHdJ gPg GdfSNI hUMMJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B72s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs